Decrease in Serum Urate Level Is Associated With Loss of Visceral Fat in Male Gout Patients - Ran, Zijing; Xue, Xiaomei; Han, Lin; Terkeltaub, Robert; Merriman, Tony R.; Zhao, Ting; He, Yuwei; Wang, Can; Li, Xinde; Liu, Zhen; Cui, Lingling; Li, Hailong; et al. (Frontiers in Endocrinology, 2021)
Objective. To clarify the relationship between serum urate (SU) decrease and visceral fat area (VFA) reduction in patients with gout. Methods. We retrospectively analyzed 237 male gout patients who had two sets of body composition and metabolic measurements within six months. Subjects included had all been treated with urate-lowering therapy (ULT) (febuxostat 20~80 mg/day or benzbromarone 25~50 mg/day, validated by the medical record). All patients were from the specialty gout clinic of the Affiliated Hospital of Qingdao University. The multiple linear regression model evaluated the relationship between change in SU (ΔSU, [baseline SU] - [final visit SU]) and change in VFA (ΔVFA, [baseline VFA] - [final visit VFA]). Results. ULT resulted in a mean (standard deviation) decrease in SU level (464.22 ± 110.21 μmol/L at baseline, 360.93 ± 91.66 μmol/L at the final visit, P <0.001) accompanied by a decrease in median (interquartile range) VFA (97.30 (81.15~118.55) at baseline, 90.90 (75.85~110.05) at the final visit, P <0.001). By multiple regression model, ΔSU was identified to be a significant determinant variable of decrease in VFA (Beta: 0.302; P=0.001). Conclusions. Decrease in SU level is positively associated with reduced VFA. This finding provides a rationale for clinical trials to affirm whether ULT promotes loss of visceral fat in patients with gout.